Clinical outcomes in pancreatic adenocarcinoma associated with BRCA-2 mutation. Issue 2 (February 2015) - Vyas, Ojas; Leung, Keith; Ledbetter, Leslie; Kaley, Kristin; Rodriguez, Teresa; Garcon, Marie C.; Saif, Muhammad W.
Abstract : Patients with BRCA-1 and BRCA-2 germ line mutations are at an increased risk of developing pancreatic adenocarcinoma (PAC). In particular, the BRCA-2 mutation has been associated with a relative risk of developing PAC of 3.51. The BRCA-2 protein is involved in repair of double-stranded DNA breaks. Recent reports have suggested that in the setting of impaired DNA repair, chemotherapeutic agents that induce DNA damage, such as platinum-based antineoplastic drugs (platins) and poly(ADP-ribose) polymerase inhibitors (PARP inhibitors), have improved efficacy. However, because of the relative rarity of BRCA-related PAC, studies evaluating such agents in this setting are scarce. Patients with a known BRCA-2 mutation and PAC were retrospectively reviewed. Ten patients with PAC and BRCA-2 mutation were identified. Four patients (40%) were of Ashkenazi Jewish descent. Seven patients (70%) received platinum agents, two (20%) received mitomycin-C, one (10%) received a PARP inhibitor, and seven (70%) received a topoisomerase-I inhibitor. Overall, chemotherapy was well tolerated with expected side effects. Patients with a BRCA-2 mutation and PAC represent a group with a unique biology underlying their cancer. Chemotherapies such as platinum derivatives, mitomycin-C, topoisomerase-I inhibitors, and PARP inhibitors targeting DNA require further investigation in this population. Genetic testing may guide therapy in the future.